Gap Analysis Sectoral Shares Index during the Covid-19 Pandemic on the Indonesia Stock Exchange - Sunarso Sunarso; Eswanto Sugeng Rahayu; Taufik Taufik; Irwan Kurniawan (LP2M Sekolah Tinggi Ilmu Ekonomi IPWI Jakarta, 2020)
The investment risk during the Covid-19 pandemic is difficult to calculate due to increasing uncertainty. The research presents a model that can be used in mitigating short-term investment risk during the Covid-19 Pandemic on the capital market with sectoral gap return base on the difference price between the highest position and the lowest position. The gap may indicate volatility, volume inequality, price abnormalities, directional anomaly, and transaction conspiracy. This paper focused on how to manage portfolio investment risk based on short-term risk mitigation base on gap Analysis of sectoral return compare to Composite Index. The aim to be achieved was to minimize the risk of short-term portfolio investment at the start of the short-term Pandemic in Januari 2020 to August 2020. The specific target to be achieved in this study is to present a model that can increase the yield of short-term investments in the Indonesia Stock Exchange with low level of risk. The object of this research was sectoral idex of stock price whose price movements are in the opposite direction to the composite stock price index. The result of this research shown that the highest gap was basic Industry sector 54,50%. Meanwhile, the lowest gap was consumer sector 22,35%. The highest the gap the bigger the risk.Keywords: Mitigation Model, Investment Risk, Stock Portfolio, Covid-19